Corollary discharge inhibition of wind-sensitive cercal giant interneurons in the singing field cricket - Schöneich, Stefan (J Neurophysiol, 2014)
Crickets carry wind-sensitive mechanoreceptors on their cerci, which, in response to the airflow produced by approaching predators, triggers escape reactions via ascending giant interneurons (GIs). Males also activate their cercal system by air currents generated due to the wing movements underlying sound production. Singing males still respond to external wind stimulation, but are not startled by the self-generated airflow. To investigate how the nervous system discriminates sensory responses to self-generated and external airflow, we intracellularly recorded wind-sensitive afferents and ventral GIs of the cercal escape pathway in fictively singing crickets, a situation lacking any self-stimulation. GI spiking was reduced whenever cercal wind stimulation coincided with singing motor activity. The axonal terminals of cercal afferents showed no indication of presynaptic inhibition during singing. In two ventral GIs, however, a corollary discharge inhibition occurred strictly in phase with the singing motor pattern. Paired intracellular recordings revealed that this inhibition was not mediated by the activity of the previously identified corollary discharge interneuron (CDI) that rhythmically inhibits the auditory pathway during singing. Cercal wind stimulation, however, reduced the spike activity of this CDI by postsynaptic inhibition. Our study reveals how precisely timed corollary discharge inhibition of ventral GIs can prevent self-generated airflow from triggering inadvertent escape responses in singing crickets. The results indicate that the responsiveness of the auditory and wind-sensitive pathway is modulated by distinct CDIs in singing crickets and that the corollary discharge inhibition in the auditory pathway can be attenuated by cercal wind stimulation.